Porous Crystalline Olefin-Linked Covalent Organic Frameworks - Lyu, Hao; Diercks, Christian S; Zhu, Chenhui; Yaghi, Omar M (Journal of the American Chemical Society, 2019)
The first unsubstituted olefin-linked covalent organic framework, termed COF-701, was made by linking 2,4,6-trimethyl-1,3,5-triazine (TMT) and 4,4′-biphenyldicarbaldehyde (BPDA) through Aldol condensation. Formation of the unsubstituted olefin (-CHCH-) linkage upon reticulation is confirmed by Fourier transform infrared (FT-IR) spectroscopy and solid-state 13C cross-polarization magic angle spinning (CP-MAS) NMR spectroscopy of the framework and of its 13C-isotope-labeled analogue. COF-701 is found to be porous (1715 m2 g–1) and to retain its composition and crystallinity under both strongly acidic and basic conditions. The high chemical robustness is attributed to the unsubstituted olefin linkages. Immobilization of the strong Lewis acid BF3·OEt2 in the pores of the structure yields BF3⊂COF-701. In the material, the catalytic activity of the guest is retained, as evidenced in a benchmark Diels–Alder reaction.